How should we manage a strong Eurasian Beaver population? A comparison of population trends in Poland and Belarus. (15th September 2022) - Yanuta, Gigorij; Wróbel, Michał; Klich, Daniel; Haidt, Andżelika; Drobik-Czwarno, Wioleta; Balcerak, Marek; Mitrenkov, Andrey
Abstract: The Eurasian beaver is currently found in at least 32 European countries, with many of these populations being established in the 1960s. In most European countries, the beaver is under protection, however, when the population is strong, the beaver becomes a game species. In Poland, the beaver is partially protected despite the species having a strong population. In this study we aimed to compare the development trends of Eurasian beaver populations in two management regimes, in Poland (protected) and Belarus (hunted), between 2004 and 2019. We compared beaver population trends in both countries, and analyzed the factors that could impact population growth. In Poland, during this period the population increased 3.5 times, while in Belarus it was only 20%. Distinct differences in the rate of population numbers increase were also observed between regions in Poland, but a stable, slight increase similar in all regions in Belarus. Our study did not show that precipitation or the density of this species influenced the rate of population development in Poland. During this period, hunting and wolf density significantly and negatively impacted beaver population growth in Belarus, but in the long-term analysis, hunting had a lower impact on beaver population growth. We concluded that we can expect a further increase in this population in Poland. Long-term hunting at a level of 13, 7% (based on the analysis of population dynamics and hunting bags for Belarus) of the annual population seems to be a safe value for the beaver population. Nevertheless more detailed analysis should be carried out in the face of the large differences between regions. Highlights: The increase in protected and used beaver populations varies. Precipitation and beaver density do not affect its growth in Poland on country level. The density of wolves limits the beaver population in Belarus on country level. Hunting at the level of 13, 7% of the annual population seems to be a safe value.